Military education past, present, and future - Kennedy, Gregory C.; Neilson, Keith (Praeger, 2002)
Often the only time a nation evaluates the education of its armed forces is during the aftermath of a great military disaster. Even in the light of an overwhelming victory, such as the Gulf War, questions about how well military education was addressing the study of asymmetric warfare, the Revolution in Military Affairs, the role of non-state actors and international relations in the new world order were the subject of debate in and around the various staff colleges and military universities in the West. This work brings together the ideas of international scholars, all recognized as leaders in their fields, to examine the professional military education experience of various nations during the last 250 years. Case studies of each branch of the military reveal success and failure in the past and present, with a goal of improving military education in the future. Underlying themes clearly reveal the need for those questioning military education to utilize history as the preferred method and model of imperial analysis. These include economics and defense spending; national psyches and the proper maintenance of armed forces; and the importance of individuals, both military and civilian, with a clear vision, determination, and the moral courage to formulate and support military education programs. In practice, training often predominates over education, and the result has frequently been an officer corps that has not functioned well in peacetime preparations and has ultimately failed on the battlefield due to an inability to think effectively. This study highlights the role of civilian educators as vital in the creation of successful educational programs.